Bronchial Washing Fluid Versus Plasma and Bronchoscopy Biopsy Samples for Detecting Epidermal Growth Factor Receptor Mutation Status in Lung Cancer - Zhang, Xinyu; Li, Chun; Ye, Maosong; Hu, Qin; Hu, Jie; Gong, Ziying; Li, Jieyi; Zhao, Xiaokai; Xu, Yiqing; Zhang, Daoyun; Hou, Yingyong; Zhang, Xin (Frontiers in Oncology, 2021)
Background: Bronchial washing fluid (BWF) is a common specimen collected during bronchoscopy and has been suggested to contain both tumor cells and cell-free DNA. However, there is no consensus on the feasibility of BWF in epidermal growth factor receptor (EGFR) genetic analysis because of the limited sample size and varying results in previous studies. This study compared the feasibility, sensitivity, and specificity of detecting EGFR mutation using BWF, bronchoscopy biopsy, and plasma samples in patients with lung cancer (LC). Materials and Methods: A total of 144 patients (110 with LC and 34 without LC) were enrolled in the study. During diagnostic bronchoscopy for suspected LC lesions, bronchial washing with saline was performed directly or through a guide sheath. BWF was collected as well as paired bronchoscopy biopsy and plasma samples, and EGFR mutation testing was performed via highly sensitive blocker polymerase chain reaction. The EGFR mutation status of histologic samples was set as the standard reference. Results: Compared with the histologic samples, the sensitivity, specificity, and concordance rate of EGFR mutation detected in BWF samples were 92.5%, 100%, and 97.9%, respectively. Moreover, BWF showed a higher sensitivity in EGFR mutation testing than both plasma (100% [8/8] vs. 62.5% [5/8], p = 0.095) and bronchoscopy biopsy samples (92.5% [37/40] vs. 77.5% [31/40], p = 0.012) and identified EGFR mutations in 6 cases whose biopsy failed to establish an LC diagnosis. The diameter of the target lesion and its contact degree with BWF were positive predictive factors for EGFR testing results. Conclusions: BWF yields a high sensitivity in EGFR mutation testing, having high concordance with histologic samples, and presenting the benefit of rapid EGFR mutation detection in LC patients.